A study of the functional assessment of the outcomes of proximal humerus fractures treated with the proximal humerus internal locking system - Yadav, Vijay; Gujar, Harshad; Pathak, Ritesh (International Journal of Research in Orthopaedics, 2025)
Background: Proximal humerus fractures are common in adults, particularly in elderly individuals with osteoporosis. Modern fixation systems such as the PHILOS (Proximal Humerus Internal Locking System) plate aim to improve stability, reduce complications and facilitate early mobilisation. To assess the functional outcomes of displaced proximal humerus fractures managed with PHILOS plating in a tertiary care hospital. Methods: This prospective observational study included skeletally mature adults (>18 years) with displaced proximal humerus fractures who underwent open reduction and internal fixation using PHILOS plating between July 2020 and July 2021. Exclusion criteria included open fractures, undisplaced fractures, fracture–dislocations limited to tuberosity, neurovascular injury and medical unfitness. Follow-up at 2, 6, 8 and 12 weeks assessed radiological union and functional recovery using the Constant–Murley Score. Data analysis was performed using IBM SPSS Statistics for Windows, Version 26.0. Results: Fifty–three patients were included with a mean age of 50 years and a male–to–female ratio of 4:1. Road traffic accidents accounted for 58.5% of injuries. Radiological union was confirmed in 96% by 12 weeks. Functional outcomes were good in 13 patients, moderate in 35 and poor in 5. Superficial wound infection occurred in 3 patients and implant failure in 1. Conclusions: PHILOS plating provides stable fixation with predominantly moderate to good short-term functional outcomes and low complication rates in displaced proximal humerus fractures.